2011
DOI: 10.1271/bbb.100541
|View full text |Cite
|
Sign up to set email alerts
|

Sake Lees Fermented with Lactic Acid Bacteria Prevents Allergic Rhinitis-Like Symptoms and IgE-Mediated Basophil Degranulation

Abstract: We tested the effect of oral administration of fermented sake lees with lactic acid bacteria (FESLAB) on a murine model of allergic rhinitis upon immunization and nasal sensitization with ovalbumin (OVA). We used Lactobacillus paracasei NPSRIk-4 (isolated from sake lees), and L. brevis NPSRIv-8 (from fermented milk) as starter strains to produce the FESLAB. Oral FESLAB administration resulted in the development of significantly fewer sneezing symptoms than those seen in sham control animals given sterile water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…MC/9 cells, a murine mast cell clone derived from mouse fetal liver (American Type Culture Collection, Manassas, VA, USA, catalogue number: CRL‐8306), were employed for the β‐hexosaminidase assay. Culture conditions and methods of the β‐hexosaminidase assay were described in detail previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MC/9 cells, a murine mast cell clone derived from mouse fetal liver (American Type Culture Collection, Manassas, VA, USA, catalogue number: CRL‐8306), were employed for the β‐hexosaminidase assay. Culture conditions and methods of the β‐hexosaminidase assay were described in detail previously …”
Section: Methodsmentioning
confidence: 99%
“…Culture conditions and methods of the β-hexosaminidase assay were described in detail previously. 14,36…”
Section: β-Hexosaminidase Assaymentioning
confidence: 99%
“…For a degranulation assay, MC/9 cells (2×10 5 cells/200 µL per well) were cultured with or without various dosages of PMB, CL, PMBN, CLMS, and compound 48/80 (a positive control; Sigma-Aldrich) for 30 min in 96-well microplates containing Tyrode's salt solution (Sigma-Aldrich). After centrifugation, supernatants were collected and degranulation was determined by a β-hexosaminidase assay as described previously [37], [38]. Briefly, supernatant samples were incubated at 37°C for 60 min with 1 mM 4-nitrophenyl N -acetyl-β-D-glucosaminide (Sigma-Aldrich) in a 0.1 M citric acid buffer (pH 4.5).…”
Section: Methodsmentioning
confidence: 99%
“…The release of total intracellular mediators was achieved by cell lysis with 0.2% Triton X-100 in Tyrode's salt solution. The percentages of released β-hexosaminidase were calculated by a formula described elsewhere [38]. Concentrations of histamine in each supernatant sample were determined by a histamine EIA kit (SPI-Bio, Montigny le Bretonneux, France).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the 'common mucosal response' concept, which introduces the idea that the alterations in immune function of the respiratory tract are linked to the immunomodulatory activity of the gut microbiome, oral administration of probiotics was used for treating allergic airway diseases by changing the gut microbiome. Some investigations have shown that the oral administration of probiotics and prebiotics may benefit allergic rhinitis patients (95)(96)(97). Moreover, the local nasal administration of Lactococcus lactis NZ9000 can affect the local and systemic immune responses against Streptococcus pneumonia (98).…”
Section: Perspectivesmentioning
confidence: 99%